2004
DOI: 10.1029/2004gl020648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a perovskite‐post perovskite phase change near core‐mantle boundary in compressible mantle convection

Abstract: [1] Numerical simulations of compressible, isochemical mantle convection are used to investigate the effect of the perovskite to post-perovskite phase transition at around 2700 km depth, which has recently been discovered by high-pressure experiments and ab initio calculations, on the convective planform, temperature, and heat transport characteristics of the mantle. The usual phase transitions at 410 km (olivine-spinel) and 660 km (spinel-perovskite) are also included. The exothermic post-perovskite phase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 20 publications
(33 reference statements)
5
53
0
Order By: Relevance
“…Previous numerical studies suggested that this phase change may have important implications in terms of dynamics and evolution of the Earth's mantle (e.g. Nakagawa & Tackley 2004, 2006Zhang & Zhong 2011;Samuel & Tosi 2012). Experimental studies (Yoshino & Yamazaki 2007;Hunt et al 2009) and first principle calculations of atomic diffusion (Ammann et al 2010) indicate that postperovskite is less viscous than perovskite by a factor of O(10 −3 ) to O(10 −4 ).…”
Section: O N C L U D I N G Discussionmentioning
confidence: 97%
“…Previous numerical studies suggested that this phase change may have important implications in terms of dynamics and evolution of the Earth's mantle (e.g. Nakagawa & Tackley 2004, 2006Zhang & Zhong 2011;Samuel & Tosi 2012). Experimental studies (Yoshino & Yamazaki 2007;Hunt et al 2009) and first principle calculations of atomic diffusion (Ammann et al 2010) indicate that postperovskite is less viscous than perovskite by a factor of O(10 −3 ) to O(10 −4 ).…”
Section: O N C L U D I N G Discussionmentioning
confidence: 97%
“…Ever since the post-perovskite phase transition was discovered, the effect of post-perovskite to the CMB heat flux and the core-mantle coupling has widely been discussed (Nakagawa and Tackley, 2004;Buffett, 2004;van der Hilst et al, 2007;Lay et al, 2008;Nakagawa and Tackley, 2008). Tackley (2004, 2008) discuss the effects of post-perovskite phase transition on the CMB heat flux in the models of thermal and thermo-chemical convection and conclude, that the deep exothermic phase change enhances heat transport.…”
Section: Discussionmentioning
confidence: 99%
“…3 we include the ppv transition. We find a general increase of mantle temperature (Matyska and Yuen, 2006;Nakagawa and Tackley, 2004) which becomes particularly evident when both depthdependent thermal expansivity and conductivity are considered (Tosi et al, 2010). Such a temperature increase is caused by the presence of ppv which greatly enhances the instability of the bottom thermal boundary layer, promoting the formation of a larger number of upwellings (compare for instance Fig.…”
Section: Global Temperature Fieldsmentioning
confidence: 72%